1992
DOI: 10.1161/01.hyp.19.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Kinins, nitric oxide, and the hypotensive effect of captopril and ramiprilat in hypertension.

Abstract: We investigated the role of kinins in the acute depressor effect of captopril and ramipriiat in spontaneously hypertensive rats. Since the vasodepressor action of kinins may be linked to the generation of prostaglandins and endothelium-derived relaxing factors, we also investigated the role of prostaglandins and nitric oxide in the blood pressure reduction caused by angiotensin converting enzyme inhibitors. To this end, we contrasted the hypotensive effects of captopril ( factors and vasodepressor prostagland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
3

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 30 publications
5
53
0
3
Order By: Relevance
“…The comparatively slow drop in blood pressure after bolus injection of perindopril is similar to the finding of Cachofeiro et al, 14 who observed that an intravenous bolus injection of ramiprilat (2 mg/kg) caused a fall in MBP that took 30 minutes to reach a maximum. The work of Richer et al 15 shows that 180 minutes after bolus injections of perindopril, the forearm resistance is reduced.…”
supporting
confidence: 87%
“…The comparatively slow drop in blood pressure after bolus injection of perindopril is similar to the finding of Cachofeiro et al, 14 who observed that an intravenous bolus injection of ramiprilat (2 mg/kg) caused a fall in MBP that took 30 minutes to reach a maximum. The work of Richer et al 15 shows that 180 minutes after bolus injections of perindopril, the forearm resistance is reduced.…”
supporting
confidence: 87%
“…Recent studies have suggested that endothelial AII AT,-receptor blockade per se enhances NO production (Sudhir et al, 1993) and upregulates endothelial NO synthase in elastic arteries (Holtz et al, 1994). Moreover, losartan as a vasodilator increases regional blood flows which through augmented shear stress may enhance NO release (Cachofeiro et al, 1992). Finally, endothelial dysfunction has been shown to be associated with hypertension (Liischer & Vanhoutte, 1986) and the possibility cannot be excluded that an 8-day treatment with losartan may have partly restored in our SHRs their impaired ability to produce NO in response to endothelium-dependent vasodilators.…”
Section: Discussionmentioning
confidence: 87%
“…Cachofeiro et al (1992) have shown in the SHR that the acute reduction in blood pressure induced by the drug is reduced by approximately 60% when the animals are pretreated with L-NMMA. Similar findings have been reported by others (Kumagai et al, 1993;Pollock et al, 1993;Sudhir et al, 1993) and in our study, L-NAME raised blood pressure and vascular resistances in losartan-treated animals.…”
Section: Discussionmentioning
confidence: 99%
“…24) Many trials including the Cooperative North Scandinavian Enalapril Survival Study, (CONCENSUS), the Studies of Left Ventricular Dysfunction (SOLVD), and the Survival and Ventricular Enlargment (SAVE) trial have demonstrated the ability of ACE inhibitors to improve hemodynamic parameters and reduce mortality within a wide range of heart failure. [25][26][27] The current study demonstrated that 3 months of cilazapril therapy improves impaired endothelium-Vol 43 No 6 dependent vasodilatation in the brachial circulation of patients with atherosclerotic diseases and heart failure. During the past two decades, it has been well established that vascular endothelium plays a pivotal role in maintaining vascular tone.…”
Section: Discussionmentioning
confidence: 84%
“…The position was maintained throughout the test, and a similar position was used in the subsequent studies. Baseline images and Vol 43 No 6 pulsed Doppler flow velocity measurements were taken (Figure). A pneumatic tourniquet was then placed proximally on the forearm and inflated to 250 mmHg of pressure for 5 minutes and rapidly deflated resulting in reactive hyperemia.…”
Section: Methodsmentioning
confidence: 99%